Nonlinear fiber optics with water wave flumes: dynamics of the optical solitons of the derivative nonlinear Schrödinger equation - Pan, Chaohong; Cheemaa, Nadia; Lin, Wenbin; İnç, Mustafa (Springer, 2024)
In this paper, we presented a novel technique called extended modified auxiliary equation mapping technique, which we used to analyze the combined Chen-Lee-Liu derivative nonlinear Schrodinger equation (MCLL-NLSE) analytically. With the help of three parameters, we were able to use our proposed method to produce newer, broader sets of exact solutions, including bright, periodic, semi half bright, dark, combined, semi half dark, doubly periodic, doubly bright, half bright, and half dark. This is the main distinction between our method and others currently in use. To develop the theoretical fluid dynamics, nonlinear fiber optics, electromagnetism, mathematical physics, bio-mathematics, soliton dynamics, plasma physics, industrial studies, quantum mechanics, nuclear physics and many other natural and physical sciences has been greatly impacted by recently discovered solutions. We have presented the newly discovered solutions in graphs in various dimensions using Mathematica 10.4 to provide a better clear picture of the dynamic properties of the solutions. Additionally, we conducted stability tests on the obtained solutions and presented them as a table.
Keywords: Graphical representation; Solitons; Combined Chen-Lee-Liu derivative nonlinear Schrodinger equation